Measuring capital intensity in South African companies listed in the Industrial Section of the Johannesburg Stock Exchange (JSE) - J. H. Burger; W. D. Hamman (South African Journal of Business Management, 1999)
The authors investigated selected listed companies in the Industrial Section of the JSE to determine the degree of capital-intensity of the selected companies. This is done by calculating various measures of capital intensity of the companies concerned and ranking the companies accordingly. Statistical analyses were done to investigate for significant differences between various measures, as well as between and within sectors of the Industrial Section of the JSE. It was found that overall there are no significant differences between the rankings of the ratios. Between sectors overall, there are significant differences between the rankings of ratios. Based upon years, however, there are no significant differences. Within sectors and between sectors per ratio, there are significant differences between the rankings of the ratios. From the analyses it is clear that the sectors are not homogeneously compiled, but are quite diversified: The measures of capital-intensity used also do not explain the same phenomenon. It has also been found that some companies display a dualism in that they are capital-intensive on some measures and capital-unintensive on others.
Keywords: 650